2007
DOI: 10.1002/dc.20600
|View full text |Cite
|
Sign up to set email alerts
|

A three‐armed trial of the ThinPrep Imaging System

Abstract: We compared the performance of the ThinPrep (TP) Imaging System (TIS) with manual reading of TP slides (TPM) and with manual reading of the paired conventional Pap smear (PS) in terms of sensitivity for and positive predictive value (PPV) of high-grade disease and productivity. The study consisted of 11,416 routine PS and paired TP slides as well as 103 confirmed abnormal TP slides. In terms of sensitivity for the detection of biopsy-confirmed high-grade disease, overall there was no statistically significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
66
3
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 8 publications
(8 reference statements)
5
66
3
1
Order By: Relevance
“…Previous data in nonrandomized settings have shown better performance of CAS compared with manually read LBC [16][17][18]28,29 and CC. 15,17 In a large prospective Australian 1 Conventional cytology: total n cytologically positives: 93 (60 histologically confirmed, 33 imputed).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous data in nonrandomized settings have shown better performance of CAS compared with manually read LBC [16][17][18]28,29 and CC. 15,17 In a large prospective Australian 1 Conventional cytology: total n cytologically positives: 93 (60 histologically confirmed, 33 imputed).…”
Section: Discussionmentioning
confidence: 99%
“…15,17 In a large prospective Australian 1 Conventional cytology: total n cytologically positives: 93 (60 histologically confirmed, 33 imputed). 2 Histologically confirmed endpoint.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This practice also has been used in trials. 2,4,6,11,[13][14][15] The idea of seeding positive cases randomly into the work to be rapid screened has been suggested by several investigators. 9 Renshaw 16 suggested that seeded cases could be used to estimate screening sensitivity.…”
mentioning
confidence: 99%